Influence of ammonium dihydrogen phosphate on potassium retention and ash melting characteristics during combustion of biomass. (1st May 2016) - Qi, Jianhui; Li, Hui; Han, Kuihua; Zuo, Qi; Gao, Jie; Wang, Qian; Lu, Chunmei
Abstract: The influence of ammonium dihydrogen phosphate (NH4 H2 PO4 ) on the potassium (K) retention ability in the ash phase and the ash melting characteristics during biomass combustion was investigated. Experiments were performed in a tube furnace experimental system and an ash melting point detector. The results show that the addition of NH4 H2 PO4 will increase the potassium retention ability in the ash phase. NH4 H2 PO4 can react with part of potassium elements within the biomass to form potassium phosphates and potassium calcium phosphates, which contributes to the improvement of the melting characteristics. Some stable double salts with high melting point are observed in the formed ashes. The feature temperatures of the formed ash were enhanced by different levels with the addition in of NH4 H2 PO4 . SEM (scanning electron microscope) analysis proved that the addition of NH4 H2 PO4 could avoid the surface melting of the formed ash. NH4 H2 PO4 is an effective biomass additive which could not only enhance the potassium retention ability in the ash phase but also enhance the ash melting characteristic of biomass. Highlights: The influence of NH4 H2 PO4 on K retention ratio and ash phase composition is studied. The micrographs and melting feature temperatures of ash are comparatively analyzed. Addition of NH4 H2 PO4 can promote K retention into biomass ash. High melting point phosphates containing K and Ca can improve ash fusibility.